New Insights into Chemical Profiles and Health-Promoting Effects of Edible Mushroom Dictyophora indusiate (Vent ex. Pers.) Fischer: A Review - Yogesh Kumar; Baojun Xu (Journal of Fungi)
Mushrooms are valued for their culinary and medicinal benefits, containing bioactive compounds like polysaccharides, terpenoids, phenolics, lectins, and ergosterols. This review aims to encourage research on D. indusiata by summarizing its chemistry, health benefits, pharmacology, and potential therapeutic applications. Molecules from D. indusiata offer anti-diabetic, antioxidant, anti-tumor, hepatoprotective, and anti-bacterial effects. In particular, polysaccharides from Dictyophora indusiata (DIP) enhance immune function, reduce oxidative stress, and promote gut health as prebiotics. DIP shows neuroprotective effects by reducing oxidative damage, improving mitochondrial function, and regulating apoptosis, making them beneficial for neurodegenerative diseases. They also activate immune responses through TLR4 and NF-κB pathways. Additionally, compounds like dictyophorines and quinazoline from D. indusiata support nerve growth and protection. Mushrooms help regulate metabolism and improve lipid profiles, with potential applications in managing metabolic disorders, cancer, cardiovascular diseases, diabetes, and neurodegenerative conditions. Their wide range of bioactive compounds makes D. indusiata mushrooms functional foods with significant therapeutic potential.